Dark Borders : Film Noir and American Citizenship - Auerbach, Jonathan, 1954- (Book collections on Project MUSE., 2011)
This title connects anxieties about citizenship and national belonging in mid-century America to the sense of alienation conveyed by American film noir. Auerbach provides interpretations of more than a dozen of these dark crime thrillers, considering them in relation to US national security measures.